Nitrogen-doped porous carbon from biomass with superior catalytic performance for acetylene hydrochlorination. Issue 25 (9th April 2020) - Shen, Zhaobing; Liu, Yue; Han, Yejun; Qin, Yejun; Li, Jinhua; Xing, Ping; Jiang, Biao
Abstract : A green, highly efficient and low-cost nitrogen-doped soybean metal carbon (SBMC) catalyst obtained from the simple carbonization of biomass soybean meal (SBM) in the presence of zinc chloride. Abstract : Acetylene hydrochlorination is an important aspect of the industrial synthesis of polyvinyl chloride, but it requires a toxic mercury chloride catalyst. Here we report a green, highly efficient and low cost nitrogen-doped soybean meal carbon (SBMC) catalyst obtained from the simple carbonization of biomass soybean meal (SBM) in the presence of zinc chloride. This material exhibits excellent catalytic performance during acetylene hydrochlorination, with an initial acetylene conversion greater than 99% and 98% selectivity for vinyl chloride at 200 °C over 110 h. Analyses by X-ray photoelectron spectroscopy and temperature programmed desorption as well as catalytic activity evaluations show that pyridinic species are the active sites for hydrogen chloride, while pyrrolic N species are the main active sites for acetylene. An analysis of charge calculations based on model catalysts further indicates that the activity of pyrrolic N species essentially determines the performance of the SBMC catalyst. This investigation of the mechanism of acetylene hydrochlorination over SBMC confirms that such nitrogen-doped catalysts have two different active sites for the adsorption and activation of hydrogen chloride and acetylene molecules. This mechanism is different from that associated with metal chloride catalysts such as HgCl2 . This SBMC catalyst is a potential alternative to HgCl2 @AC catalysts for vinyl chloride synthesis and suggests a new means of designing carbon catalysts with basic surfaces for acetylene hydrochlorination.